1996
DOI: 10.1152/ajpendo.1996.271.6.e1083
|View full text |Cite
|
Sign up to set email alerts
|

Acute postprandial changes in leucine metabolism as assessed with an intrinsically labeled milk protein

Abstract: Mechanisms of protein gain during protein feeding have been investigated using a combination of oral and intravenous labeled leucine in healthy young men. The oral labeled leucine was administered as a free oral tracer ([13C]- or [2H3]leucine) added to unlabeled whey protein or as whey protein intrinsically labeled with L-[1-13C]leucine. When the oral tracer was free leucine, it appeared in the plasma more rapidly than the unlabeled leucine derived from the whey protein, and this resulted in an artifactual 88%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
152
0
2

Year Published

1999
1999
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(164 citation statements)
references
References 11 publications
10
152
0
2
Order By: Relevance
“…When the non-steady-state equations of Shipley & Clarke (1972) were applied to the fasting± feeding data of el Khoury et al (1995b), taking account of changes in the plasma leucine concentration as a measure of changes in the free leucine pool, the increase in synthesis in response to a meal was substantially greater than that obtained by the usual method of calculation (Waterlow, 1995). This conclusion is supported by a study of Boirie et al (1996), who fed a single meal containing labelled protein. Applying the non-steady-state equations, they showed that the response to the meal was an increase in synthesis with little change in breakdown.…”
Section: Fasting and Feedingmentioning
confidence: 72%
“…When the non-steady-state equations of Shipley & Clarke (1972) were applied to the fasting± feeding data of el Khoury et al (1995b), taking account of changes in the plasma leucine concentration as a measure of changes in the free leucine pool, the increase in synthesis in response to a meal was substantially greater than that obtained by the usual method of calculation (Waterlow, 1995). This conclusion is supported by a study of Boirie et al (1996), who fed a single meal containing labelled protein. Applying the non-steady-state equations, they showed that the response to the meal was an increase in synthesis with little change in breakdown.…”
Section: Fasting and Feedingmentioning
confidence: 72%
“…Additionally in humans, the ingestion of rapidly absorbed whey proteins results in an enhanced postprandial whole body protein synthesis and oxidation rate than those measured following the ingestion of the slowly absorbed casein. Since the oxidation rate is increased to a greater extent than the synthesis rate, this leads to a reduced net 13 C-leucine balance during the 7 h following the meal [2,32]. This suggests that the postprandial protein deposition would be reduced with non clotting diets as compared to clotting ones.…”
Section: Discussionmentioning
confidence: 99%
“…Total, exogenous, and endogenous phenylalanine rate of appearance (R a) and plasma availability of dietary phenylalanine (i.e., fraction of dietary phenylalanine that appeared in the systemic circulation, Pheplasma) were calculated using modified Steele's equations (6,9). These parameters were calculated as follows:…”
Section: H5]phenylalanine and L-[ring-mentioning
confidence: 99%
“…So far, no study has assessed the impact of ingesting different amounts of whey protein on protein digestion and absorption kinetics, whole body protein balance, and postprandial muscle protein synthesis rates in older adults. Because the metabolic fate of amino acids ingested as dietary protein cannot be assessed by oral or intravenous administration of labeled free amino acids (6,8), we specifically produced intrinsically labeled whey protein by infusing cows with large quantities of L- [1-13 C]phenylalanine, collecting milk, and purifying the whey protein fraction (21). The use of intrinsically labeled whey protein allowed us to assess the impact of ingesting different amounts of whey protein on in vivo protein digestion and absorption kinetics and subsequent muscle protein accretion without the need for extensive assumptions and extrapolations.…”
mentioning
confidence: 99%